SpeechKit: a multimedia speech tool - Calder, David (Association for Computing Machinery (ACM), 2008)
SpeechKit is a multimedia system for use by speech therapists to assist in the rehabilitation of motor impaired patients. These are often stroke victims who have to relearn the ability to communicate effectively. The process is laborious and usually conducted in a one-to-one situation where interaction between therapist and client depends on visual and audio cues. Instead of the usual paper-based prompts used by the therapist, this multimedia solution offers screen prompts together with high quality digitised speech. The result is a reduced work load for the therapist. The system has undergone beta tests in Western Australia. The well established and robust Asymetrix Toolbook was used for development of the speech therapy tool, the current version in mid 2008 being version 9.1.